2020
DOI: 10.21203/rs.3.rs-42369/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Research of insomnia on traditional Chinese medicine diagnosis and treatment based on machine learning

Abstract: Background: Insomnia as one of the dominant diseases of traditional Chinese medicine (TCM) has been extensively studied in recent years. To explore the novel approaches of research on TCM diagnosis and treatment, this paper presents a strategy for the research of insomnia based on machine learning. Methods: First of all, 654 insomnia cases have been collected from an experienced doctor of TCM as sample data. Secondly, in the light of the characteristics of TCM diagnosis and treatment, the contents of research … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Western Medicine recommended medications for insomnia are effective, but long-term administration is often accompanied by adverse effects [10,11]. Currently, traditional Chinese medicine is regarded by many researchers and has been largely studied due to its high safety, minimal side effects, and acceptability [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Western Medicine recommended medications for insomnia are effective, but long-term administration is often accompanied by adverse effects [10,11]. Currently, traditional Chinese medicine is regarded by many researchers and has been largely studied due to its high safety, minimal side effects, and acceptability [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia refers to a subjective experience that patients still have difficulty falling asleep or insufficient sleep depth or difficult to maintain sleep when they have sufficient sleep opportunities and comfortable sleep environment, and it seriously affects their study, work and life [1] . With the development of social economy, the change of lifestyle, and the increasing incidence of insomnia in China, the number of adults who meet the diagnostic criteria of insomnia is as high as 10% -15%, and about 50% of them can last for more than 10 years [2] insomnia often occurs repeatedly, showing a chronic course, and long-term insomnia is a risk factor for a variety of diseases, which can greatly increase the risk of cardiovascular and cerebrovascular diseases, endocrine diseases, tumors and other diseases. Serious insomnia can also lead to reduced work efficiency, reduced attention and alertness, greatly increasing the incidence of accidents among high-risk workers, causing huge economic losses and personal safety threats [3] .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16] In recent years, several studies have summarized the characteristics of symptoms in TCM and found that diagnosis in TCM can be achieved by bionics instruments. [17][18][19] The application of ICT in the field of medicine and health has become normal, and several TCM doctors have begun using devices as diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%